The Srōš Drōn - Yasna 3 to 8 - Redard, Céline. (Leiden ; Boston)
xx, 543 sayfa
Keywords: “This book is a multi-faceted study of the Srōš Drōn, comprising chapters 3 to 8 of the Yasna ceremony, the core ritual of the Zoroastrian religions. It provides a critical edition produced with the electronic tools of the project The Multimedia Yasna, and a study of the performative aspects of the Srōš Drōn both through the lens of the ritual directions and in comparison with the Drōn Yašt ceremony. By analysing the Srōš Drōn both as a text attested in manuscripts and as a ritual performance, Céline Redard applies a new approach to unlock the meaning of these chapters of the Yasna“ --